2017
DOI: 10.1038/s41598-017-01832-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of FAK-ERK2 signaling pathway in CKAP2-induced proliferation and motility in cervical carcinoma cell lines

Abstract: Cervical carcinoma is the fourth most common cause of death in woman, caused by human papillomavirus (HPV) infections and arising from the cervix. Cytoskeleton-associated protein 2 (CKAP2), also known as tumor-associated microtubule-associated protein, has been linked to tumorigenic effects. In the present study, we screened CKAP2 as a new candidate gene which promotes development of cervical carcinoma, in two independent datasets (TCGA and GSE27678). Results showed that CKAP2 expression was significantly up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…These findings overall suggest that loss of JAM-A promotes keratinocyte proliferation and migration, and the in vivo healing course, which is regulated by the signaling of FAK-mediated Erk1/2 activation. It is worthy to note that although the half-life of PF-562271 or PD98059 is not specified by the manufacturer, the working concentration and treatment duration regarding these two drugs are selected with great caution based on several important literatures 16 , 17 , 24 , 25 and our pilot experiments. The optimum concentration and treatment duration of JAM-A siRNA duplexes were also carefully selected based on our previously published works 26 and preliminary data, we found that transfection of keratinocytes with 100 nM JAM-A siRNA duplex (50 nM seq#1 + 50 nM seq#2, see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings overall suggest that loss of JAM-A promotes keratinocyte proliferation and migration, and the in vivo healing course, which is regulated by the signaling of FAK-mediated Erk1/2 activation. It is worthy to note that although the half-life of PF-562271 or PD98059 is not specified by the manufacturer, the working concentration and treatment duration regarding these two drugs are selected with great caution based on several important literatures 16 , 17 , 24 , 25 and our pilot experiments. The optimum concentration and treatment duration of JAM-A siRNA duplexes were also carefully selected based on our previously published works 26 and preliminary data, we found that transfection of keratinocytes with 100 nM JAM-A siRNA duplex (50 nM seq#1 + 50 nM seq#2, see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CKAP2 has been observed to have an oncogenic function in CC development, based on TCGA data, and this is likely accomplished via its interference with FAK-ERK2 signaling [ 44 ]. Another gene detected in this study to be involved in CC pathogenesis is DUOX1.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of early-stage breast cancer, high CKAP2 expression was revealed to promote the proliferation of tumor cells and significantly shorten relapse-free survival ( 17 ). Additionally, overexpression of CKAP2 activates the focal adhesion kinase (FAK)-extracellular signal-regulated kinase 2 signaling pathway, and induces cell proliferation and migration; however, this effect can be blocked by FAK inhibitors ( 18 ). In addition to CKAP2, other members of the CKAP family have also demonstrated similar effects on tumor cells, including CKAP4.…”
Section: Discussionmentioning
confidence: 99%
“…CKAP2 was recently reported to be a substrate of cyclin-dependent kinase (CDK)1-cyclin B and was indicated to be essential for bipolar spindle formation ( 14 ). The oncogenic nature of CKAP2 in the occurrence and development of gastric ( 15 ), ovarian ( 16 ) and breast cancer ( 17 ), and other malignant tumors ( 18 ā€“ 21 ) has been elaborated. However, limited studies have assessed the biological characteristics and significance of CKAP2 in HGG.…”
Section: Introductionmentioning
confidence: 99%